'Man in makeup': The new gender concept in James Charles' Instagram posts - Saktiana Kharisma Ardiani; Sri Kusumo Habsari (Universitas Sebelas Maret, 2020)
The rise of ‘man in makeup’ trend in online platforms has brought male makeup artists to break down the gender stereotype and discrimination in beauty industry. Here, the research focused on a male makeup artist, James Charles, on his Instagram account, who brings the concept of ‘man in makeup’ to reject the transgender label. The research examined the way James Charles presents his gender concept, ‘man in makeup’ through his cultural practices on Instagram. The research shows that James Charles has failed in following the male role norms. However, this failure cannot put James Charles to crisis of masculinity. This happens because James Charles has negotiated the male role norms with the self feminizing. Thus, the feminine notion of makeup is not contradictory with his feminized male body, gestures, and identity. At the end, this research argues that ‘man in makeup’ gender concept has been accepted by the Instagram users.